Ultrasound Studies of COVID-19–Positive Patients and Patient Under Investigation: Pandemic Experience of Body Imaging Division at a Tertiary Medical Center. Issue 3 (September 2021) - Gawande, Rakhee S.; Vadvala, Harshna V.; Shan, Alan; Sheth, Sheila
Abstract : Abstract: This retrospective study shares our departmental experience of screening of ultrasound (US) requests, triaging of studies, and abbreviated US protocols implemented during the COVID-19 pandemic. For US studies requested in April and May 2020, the following data were collected: type of study, indication, COVID-19 status (positive or patient under investigation [PUI]), decision to perform study, US findings, and location of patient. A total of 196 US studies in 150 patients were included. The median age of patients was 60 years (female: 46.7% [70/150]). At the time of study request, 83 patients (55.3%) were COVID-19–positive and 67 (44.7%) were PUI, of which 8 (11.9%) tested positive after waiting for test result. The most frequently requested study was venous extremity Doppler (51%), followed by right upper quadrant (20.4%), renal (11.7%), and liver duplex (6.6%). After radiologist screening and triage of US requests, 156 studies were performed (79.6%), 15 were postponed until COVID test result (7.6%), and 40 were not performed after discussion with ordering provider (20.4%). Notably, 40.1% of studies performed on COVID-19–positive patients yielded pathological findings, most frequently deep venous thrombosis (18.1%), medical renal disease (7.6%), and gall bladder sludge (5.7%). Abbreviated US protocols were used in 29.4% of studies. In conclusion, US study screening and triage played an important role to optimize care of COVID-19 patients and PUIs.